Naître, aimer, mourir. Les lits (et leurs habitants) dans la peinture bolonaise des xvie et xviie siècles - Michele Danieli (In Situ)
Some examples taken from the paintings executed at Bologna from the end of the sixteenth century to the end of the seventeenth illustrate the different meanings that can be attributed to the bed in different narrative contexts. The bed can become a major theatrical scene on which Orazio Samacchini rewrites a famous episode from the Aeneid, giving special emphasis to its sensitive and intimate character. The female figures in the paintings of Denis Calvaert live tragic adventures, but with varying outcomes. The moral rectitude of Lucretia or the recklessness of Semele impose appropriate settings and for each one, the artist choses the bed that is most suitable. The bed that Lorenzo Sabatini includes in his painting has purely symbolic significance which the painter uses in order to enrich his allegorical representation. The absence of a court and a centre of private power at Bologna during the early modern period means that it was not a centre for the production of furniture for a sovereign’s residence. So, the paradigm of luxury furniture is to be looked for in the mannerist painting of Florence or Rome or in Flemish engravings, articles that were more accessible to artists than the real royal objects. This is clearly demonstrated in a painting by Lavinia Fontana, which is a proper ‘portrait’ of a bed. The spectacle it offers of real affluence distinguishes this painting from the others examined here.